Uranium metabolism associated with ontogenetic growth of birds: case studies with broilers and ducks - Arruda-neto, Joao Dias de Toledo; Cavalcante, Guacyara Tenorio; Paula Nogueira, Guilherme de [UNESP]; Rodrigues, Tulio Eduardo; Fonseca, Luiz Eduardo Corrêa [UNESP]; Saiki, Mitiko; Genofre, Godofredo Camara (Scientific Research, 2014)
Cobb broilers and domestic ducks, both one-day-old, were treated using ration doped with 20 ppm of uranyl nitrate. Uranium concentrations in the tibia (μg-U/g-bone) were measured by neutron activation analysis as function of the animals’ age, from the neonatal period to maturity. Results show that Uranium and Calcium qualitatively follow the same metabolic pathway, and that adult ducks incorporate on average ten times more Uranium than broilers. Data interpretation shows that the Uranium clearance rate in broilers is substantially higher than that in ducks, suggesting that metabolic characteristics favoring Calcium retention in bone may hinder the elimination of Uranium in ducks. The need for further comparative biochemistry studies between Galliformes and Anseriformes is addressed.
Keywords: Cobb broilers; Domestic ducks; Uranium-doped-ration; Uranium-content in bones; U/Ca metabolism; Uranium residence times